Distinct behaviors of KNO3 and NaNO3 in specific heat enhancement of molten salt nanofluid - Jeong, Seonjin; Jo, Byeongnam (Journal of Energy Storage, 2023)
This study aims to examine the effects of the solvent of molten salt nanofluids on the specific heat capacity (SHC) and furthermore to understand the mechanism for enhanced SHC of the nanofluids. Moreover, the effects of the electrical double layer (EDL) on the SHC enhancement were quantitatively analyzed for a single salt and binary salt-based nanofluids. Two different nanoparticles, SiO2 and graphite, were dispersed in sodium nitrate (NaNO3), potassium nitrate (KNO3) and NaNO3-KNO3 mixtures. The SHC of the nanofluids was experimentally measured by a differential scanning calorimetry. The SHC of the NaNO3-SiO2 nanofluids was increased up to 17.2 % in liquid phase, whereas the SHC enhancements of the binary salt-SiO2 nanofluids were varied between-1.2 and 8.2 % in liquid phase. Additionally, the SHC enhancement was unfavorably proportional to the mass ratio of NaNO3 in the binary salt-SiO2 nanofluids. In graphite nanofluids, the SHC was enhanced up to 20.1 % and 7.1 % in KNO3 and NaNO3, respectively. However, the enhancement in the SHC was <7.8 % in the binary salt-graphite nanofluids. The zeta potentials of the SiO2 nanoparticle in the aqueous salt solution were linearly increased with the composition of NaNO3 which can be correlated with the salt solvent dependent SHC in the binary salt nanofluid. Finally, the EDL analysis indicates that SiO2 nanoparticles have stronger attractive force in ionic solutions than graphite. Furthermore, the EDL interactive forces demonstrate that the potential energy in the EDL adjacent to the nanoparticles determines the SHC enhancement of the molten salt nanofluids. Keywords: Nanofluid Specific heat Molten salt Zeta potential Electric double layer Interaction potential energy
Keywords: Binary salts; Capacity enhancement; Electrical double layers; Heat enhancement; Liquid Phase; Liquid phasis; Mass ratio; Molten salt; Nanofluids; Specific heat capacity